MODEL SISTEM MONITORING KEPADATAN SAMPAH DENGAN MIKROKONTROLER BERBASIS ANDROID - Chani Abdi Satria (2020)
Increasing the population produces serious problems with garbage. We often encounter this garbage problem in our beloved country and it will be more serious if not handled properly. The local government has assigned to transport garbage from each house. However, it is less effective because it is taken once every 2 days, so that residents of the housing area let trash accumulate beyond the container limit. To overcome this problem a monitoring system is needed to monitor waste density. HCSR-04 Ultrasonic Sensor integrated with the NodeMCU ESP8266 microcontroller. The system that has been built is capable of displaying the height of waste data, providing information on the condition of the trash, and can determine the status of empty to full garbage by providing accurate notifications. This system is also connected to the internet so monitoring can be done anytime and anywhere.